Harlem Calypso and Brooklyn Soca: Caribbean Carnival music in the diaspora*. Issue 6 (26th April 2019) - Allen, Ray
ABSTRACT: This query examines the history of Harlem calypso in the 1920s and 1930s, and Brooklyn soca music in the 1980s. Unfolding in the context of diasporic Caribbean Carnival celebrations, the evolution of these distinctive music styles provides a window into the dynamic nature of twentieth century cultural globalization. Specifically, the development of Harlem calypso and Brooklyn soca demonstrate how music can serve as an essential connecting thread in the formation of the modern transnation. The validity of the terms "center" and "periphery, " when used in reference to the new, globally connected world, is challenged. The need for more nuanced models that stress the dialogical, cyclical movement of cultural actors and their expressions between the Caribbean homeland(s) and urban diasporic communities is stressed.